The Effect of Arduino-Based E-STEM Education on Students' Entrepreneurial Skills and STEM Attitudes - Tolga Topcubaşi; Aydın Tiryaki (Universitas Pendidikan Indonesia, 2023)
The research aims to determine the effect of Arduino-based E-STEM education on entrepreneurship skills and STEM attitudes of 4th-grade students within the scope of science and social studies education. This research was designed within the framework of the nested pattern of the mixed research method.